Pendidikan Agama Islam berbasis Ecotheology Islam untuk Mewujudkan Kesadaran Lingkungan - Laksono, Gangsar Edi (Jurnal Kependidikan, 2022)
PAI learning has a strategic role to internalize the value of environmental awareness because it must be given at all levels of education. This study aims to formulate goals and steps in realizing environmental awareness through ecotheology-based PAI learning originating from the Al-Quran and hadith. This research used a descriptive qualitative method with a type of library research. The data or materials used in this study come from books, journals, research results, documents, magazines and other library sources. The data collection technique used was documentary source documentation from various literary sources and then analyzed using content analysis. The purpose of ecotheology-based PAI learning is not only in the cognitive domain but in the aspect of increasing awareness, attitudes, skills and participation so that it leads to ecologically responsible morals and morals. In realizing this goal, the formulated strategy must implement aspects of learning materials, learning strategies, models and support for educational institutions/schools or madrasahs.